PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN PERKARA DALAM KEBAKARAN HUTAN DAN LAHAN - Hanipah; Kadaryanto, Bagio; Harahap, Irawan (The Juris, 2024)
The judge decided on Article 99 in a case and chose to rule based on Article 99 paragraph (1), indicating that the judge assessed the environmental violation as being caused by negligence rather than intent. Therefore, the punishment imposed is lighter compared to the sanctions under Article 98 paragraph (1), although still severe, considering the environmental impact caused. The purpose of this study is to analyze the legal considerations of judges in their decisions on forest and land fire cases and to examine the legal provisions concerning the criminal act of forest and land burning in Indonesia. The method used is normative legal research. Based on the research findings, it was revealed that the legal considerations of judges in decisions on forest and land fire cases involve assessing various legal aspects and evidence presented during the trial. The judges evaluate whether the defendant’s actions fulfill the elements of a criminal act as stipulated in the relevant laws. Proof of intent, negligence, and the impact of the fire are crucial aspects. The verdict is also influenced by the extent of environmental damage, the impact on public health, and the economic losses incurred. Additionally, the judge considers the defendant’s active role or negligence in preventing the fire. In some rulings, as in the above case, although the defendant burned the land on orders from another party, malicious intent or intent was not found. Regarding the legal provisions for forest and land burning in Indonesia, Law Number 32 of 2009 strictly prohibits such acts. Article 69 paragraph (1) letter h prohibits land clearing by burning, while Article 108 stipulates criminal sanctions for offenders with imprisonment ranging from 3 to 10 years and fines varying from IDR 3 billion to IDR 10 billion. Harsher penalties are imposed if the act causes environmental pollution or endangers human health, as regulated in Articles 98 and 99. In cases where burning causes serious injury or death, the punishment can reach 15 years in prison and fines of up to IDR 15 billion. Additionally, business entities found guilty of this crime may face additional sanctions such as license revocation.